Melanocyte-specific expression of the human tyrosinase promoter: activation by the microphthalmia gene product and role of the initiator. - Bentley, N J (1994)
The tyrosinase gene is expressed specifically in melanocytes and the cells of the retinal pigment epithelium, which together are responsible for skin, hair, and eye color. By using a combination of DNase I footprinting and band shift assays coupled with mutagenesis of specific DNA elements, we examined the requirements for melanocyte-specific expression of the human tyrosinase promoter. We found that as little as 115 bp of the upstream sequence was sufficient to direct tissue-specific expression. This 115-bp stretch contains three positive elements: the M box, a conserved element found in other melanocyte-specific promoters; an Sp1 site; and a highly evolutionarily conserved element located between -14 and +1 comprising an E-box motif and an overlapping octamer element. In addition, two further elements, one positive and one negative, are located between positions -185 and -150 and positions -150 and -115, respectively. We also found that the basic helix-loop-helix factor encoded by the microphthalmia gene, which is essential for melanocyte differentiation, can transactivate the tyrosinase promoter via the M box and the conserved E box located close to the initiator. Since in vitro assays failed to identify any melanocyte-specific DNA-binding activity, the possibility that the specific arrangement of elements within the basal tyrosinase promoter determines melanocyte-specific expression is discussed.